Influence of stacking sequence on impact strength/hardness of CF/GF hybrid composites fabricated by VARIMC technique. (2021) - Kumar, Rajeev; Rani, Manjeet; Zafar, Sunny
Highlights: Hybrid CF/GF laminates were fabricated using vacuum assisted resin infusion microwave curing technique. Laminates at various stacking sequences were tested for hardness and imact strength. Three types of failures i.e. matrix cracking, fiber cracking and delamination of laminates took place during testing. Best stacking sequence for hybrid laminate was reported with GF fiber placed at outer surface of laminate. Abstract: For light weight and high strength applications, different types of fibers such as carbon fiber (CF), glass fiber (GF) and Kevlar fibers are stacked layer by layer to fabricate low density laminates. This process is known as hybridization and fabricated composites are called hybrid composites. These types of composites used in high structural applications. Hybrid composites are known for their high strength to weight ration and ability to absorb energy. In present work, Izod impact and shore-D hardness response of hybrid composites (GF and CF reinforced polymer matrix) were investigated. Hybrid composites with different stacking sequence of CF and GF were fabricated by vacuum assisted resin infusion microwave curing (VARIMC) process. Bidirectional woven fabrics of CF and GF was used. Three types of stacking sequence (CGCGCGC)3, (C2 G3 C2 )3 and (GC2 GC2 G)3 was used for hybrid composites. According to ASTM standard for testing, the thickness of the laminates was maintained about 6 mm. Results revealed that the variation of impact strength was strongly depends on lay-up stacking sequence of GFs and CFs in hybrid composite laminates. Three modes of failure of laminates i.e., matrix cracking, fiber breakage and delamination were observed.